Analysis of the Application of Safety and Health Management System Work Against a Work Behavior and Conditions of the Work Environment in the dr. Harjono General Hospital of Ponorogo - Fresvian Jenrivo; Indasah Indasah; Nurwijayanti Nurwijayanti (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
The occurrence of accidents at work is largely caused by human factors (unsafe act), i.e., the behavior that is not secure. And the fraction is caused by environmental factors (unsafe condition). Therefore, to ensure the safety and health of the medical personnel, non-medic personnel nor others who visited the hospital, it takes an effort to minimize the risk of danger that exists, it needs to be applied to the safety management system and Occupational Health Hospital. The purpose of this research was to analyze the effect of the application of safety and health management system Work Against a work Behavior And environmental conditions of work at the Dr. Harjono General Hospital of Ponorogo. The research design was analytic observational with a quantitative approach. Research on variable i.e. application of the occupational health and safety management system (OHSMS) as the independent variable, the behavior of the working conditions and working environment as the dependent variable. This research population all employees in installations of polyclinics, inpatient care installations, medical record and pharmaceutical installation Dr. Harjono General Hospital of Ponorogo as many as 446 employees. Samples taken with the cluster random sampling technique as much as 258 respondents. Data is collected with instruments ceklist and processed in coding, editing, tabulating and scoring as well as tested with linear regression test. Linear regression results indicate that partially and simultaneously the value of p values there are shows so that 0.05 < influence influence the application of safety and health management system Work Against a work Behavior And Work in environmental conditions at Dr. Harjono General Hospital of Ponorogo. The existence of the application of management system of safety and occupational health will create the most benefits to the maintenance of a good workforce that can be seen from the behavior of the work and the working environment